Effect of Trade Liberalization on Economic Growth in the Panel of ASIAN Economies - Imran Ullah; Muhammad Tufail; Muhammad Rafiq (Journal of Business & Tourism, 2021)
The present study has investigated the effects of the trade liberalization on the Economic Growth of ASIAN economies. For the sake of investigation, we took the data from 1985 to 2014 for empirical analysis, which is based on a panel of 34 countries. We have estimated the dynamic panel estimation was performed and for this purpose Generalized Method of Moment (GMM) was used. The findings of the current study have confirmed that the openness impact on the growth of economics is positive. As the openness allow utilization of comparative advantage, diffusion of knowledge, increasing scale of economies, technology transfer and exposure to competition. It is therefore, suggested that government should take prudent steps to further liberalize the trade to gain from trade